1989
DOI: 10.1161/01.cir.80.6.1675
|View full text |Cite
|
Sign up to set email alerts
|

Diverse mechanisms of unexpected cardiac arrest in advanced heart failure.

Abstract: To define the mechanisms of unexpected cardiac arrest in advanced heart failure, we reviewed the causes of cardiac arrest as established from electrocardiographic monitoring and from clinical and autopsy data in patients hospitalized for cardiac transplantation evaluation and management of advanced heart failure (mean left ventricular ejection fraction, 0.18 +/- 0.08) who were stable while on vasodilator and diuretic therapy such that hospital discharge to home was anticipated. Twenty-one cardiac arrests occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
1
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 483 publications
(171 citation statements)
references
References 32 publications
7
154
1
7
Order By: Relevance
“…One series showed that 62% of such patients had severe bradycardia or electromechanical dissociation as the underlying cause for their SCD and only 38% had ventricular tachycardia/ventricular fibrillation. 17 In other uncommon causes of nonischemic cardiomyopathies, such as infiltrative (sarcoidosis), genetic (arrhythmogenic right ventricular cardiomyopathy), and inflammatory/immunologic (acute myocarditis or Chagas disease), SCD is almost always caused by ventricular arrhythmias. In patients with sarcoidosis, myocardial involvement may be multifocal and the sarcoid granulomas become foci of abnormal automaticity and increase the likelihood of reentrant arrhythmias.…”
Section: Pathophysiologymentioning
confidence: 99%
“…One series showed that 62% of such patients had severe bradycardia or electromechanical dissociation as the underlying cause for their SCD and only 38% had ventricular tachycardia/ventricular fibrillation. 17 In other uncommon causes of nonischemic cardiomyopathies, such as infiltrative (sarcoidosis), genetic (arrhythmogenic right ventricular cardiomyopathy), and inflammatory/immunologic (acute myocarditis or Chagas disease), SCD is almost always caused by ventricular arrhythmias. In patients with sarcoidosis, myocardial involvement may be multifocal and the sarcoid granulomas become foci of abnormal automaticity and increase the likelihood of reentrant arrhythmias.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Also in some cases of idiopathic VT, enhanced vagal tone has been suggested to be profibrillatory. 96,97 Less serious but important common side effects that have been reported from VNS include a cough, neck pain, swallowing difficulty or change in voice. In addition, procedural complications are certainly possible.…”
Section: Potential Adverse Effects Of Vagal Stimulationmentioning
confidence: 99%
“…In addition, the majority of SCDs occur at home, often where the event is unwitnessed [18,19]. SCD can manifest as ventricular tachycardia (VT), ventricular fibrillation (VF), that accounting for approximately three-quarters of cases, the rest 25% caused by bradyarrhythmias or asystole [20][21][22]. In a significant proportion of patients, SCD can present without warning or a recognized triggering mechanism.…”
Section: Sudden Cardiac Deathmentioning
confidence: 99%